Analysis of Open-Source Solution for Point of Sales Inventory Management System - Marico, Joxel; Purnama, James; Galinium, Maulahikmah (Conference Series, 2021)
Package other popular food distributor businesses. To gain advantage, they used newest Point of Sales (POS) for their business. POS allows user mood to do transaction between buyer and cashier, manage stock, etc. Unfortunately after several months, their business closed down, because the newest POS is not designed for their food distributor. ,The purpose of this research is to understand how POS would affect the business and why POS is valuable and important for business. The goal of this research is to find out which POS is suitable for both small and large business. There are four open-source POS to be analyzed, which are Odoo, E-hopper, Loyverse and Aronium. fOr Comparing Open Source software Evaluation Methods (FOCOSEM) is used to compare their features. In conclusion, only one shop. If the business owner wants to open another shop at different location but he/ she wants to keep track another shop, E-hopper or Loyverse is recommended. If the business owner wants to use mobile devices for easy setup, Loyverse is recommended. If the business owner prefers using PC, then E-hopper is recommended. For business owner who is conducting export and import then Odoo is recommended.